(When) Does tit-for-tat diplomacy in trade policy pay off? - Barbara Dluhosch; Daniel Horgos (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2012)
In international relations, short-run incentives for non-cooperation often dominate. Yet, (external) institutions for enforcing cooperation are hampered by national sovereignty, supposedly strengthening the role of selfenforcing mechanisms. This paper examines their scope with a focus on contingent protection aka tit-for-tat in trade policy. By highlighting various strategies in a (linear) partial-equilibrium framework, we show that retaliation of noncooperative behavior by limiting market access works as a disciplining device independently of supply and demand parameters. Our theoretical results are backed by empirical evidence that countries more frequently involved in WTO-mediated disputes entailing tit-for-tat strategies pursue on average more liberal trade regimes.
urn:nbn:de:gbv:705-opus-29702
Keywords: F13; F51; D74; 330; Int. Political Economy; Trade Policy Conflicts; Tit-for-Tat; WTO Dispute Settlement